PENGARUH PENERAPAN e-SPT DAN TINGKAT PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KPP PRATAMA BANDUNG CICADAS - Eko Purwanto; Yeyen Marito Hutasoit (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2019)
This study aims to determine the effect of the application of e-SPT and the level of understanding of taxation on individual taxpayer compliance at KPP Pratama BandungCicadas. This type of research is in the form of quantitative research using descriptive analysismethods. The population in this study is an individual taxpayer registered at the BandungCicadas Primary Tax Office as many as 79,820 individual taxpayers. Sampling usedprobability sampling by using random sampling as many as 100 individual taxpayers. Theresults of this study indicate that the application of e-SPT has a partial effect on individualtaxpayer compliance of 2,194 (tcount) > 1,985 (t table) and the level of understanding oftaxation has a partial effect on taxpayer compliance personal amount of 4,573 (tcount) > 1,985(t table). The application of e-SPT and the level of understanding of taxation in a simultammanner affect individual taxpayer compliance at KPP Pratama Bandung Cicadas in theamount of 30,543 (Fcount)> 3,090 (Ftable).